"That Old Black Magic": Noir and Music in Juan Díaz Canales and Juanjo Guarnido's Blacksad. Issue 1 (31st July 2019) - Austin, Hailey J.
Abstract : Juan Díaz Canales and Juanjo Guarnido's Blacksad is a comic series that evokes the noir tradition through thematic and visual callbacks to noir films and comics. As they use noir tropes, the comics illuminate the tensions in both noir and comics. Yet, Blacksad stands out as a liminal text that simultaneously references and reverses traditional noir themes. One often-overlooked noir trope is the inclusion of music in each comic album. Blacksad has often been analysed as a purely visual text. However, the inclusion of music enhances the text as the songs themselves create a layered meaning in the work that is relevant to the styles present in both comics and film noir. The music enhances the intertextual and noir references embedded in Blacksad, both building the world around the story and enhancing the storytelling of an inherently 'silent' medium.